The Effectiveness and Mechanisms of China’s Grain Support Policies in Relation to Grain Yield—An Evaluation of a Wide Range of Policies - Tianjian Li; Fan Yang; Haotian Zhang; Qingning Lin (Foods)
Objective evaluation and in-depth systematic analysis of the effectiveness of implementing a grain support policy series represent an important entry point for improving incentives to grow food, improving grain production support and protection systems, and guaranteeing national food security. Thus, we collected and organized grain support policies during the study period according to the government work reports of 31 provinces in China from 2001 to 2022 and applied a two-way fixed-effects model based on the variables constructed using textual analysis to further explore the effects of a range of grain support policies on grain production gains. The conclusions are as follows: (1) grain support policies significantly contributed to an increase in grain production; (2) grain production gains from grain support policies are more pronounced in less industrialized and disaster-affected areas; (3) a mechanism analysis showed that grain support policies enhanced grain production by expanding the scale of food cultivation, upgrading agricultural mechanization, and strengthening soil erosion control; and (4) further analysis showed that grain support policies increased pesticide use. These conclusions are of great significance for improving grain production support and protection systems, enhancing incentives for farmers to grow food and for local governments to control food, and achieving the goal of food security.